Reading in Modern Ukraine: Popularization Practices - Курушина, Марина (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The paper focuses on the main practices of reading in modern Ukraine. The main features of mass-media resources about literature were studied (newspaper, athenaeums, sites, social media sites etc.). The events for popularization were named (like festivals, forums, discussions, literary prizes, summer schools, workshops etc.). Integration of modern reading and other leisure services, the realization of this idea in the modern city were stressed. The author came to conclusion about variety in form and in content of the ways in popularization of reading.